Pengaruh Penggunaan Influencer marketing dan Kualitas Produk Terhadap Keputusan Pembelian Melalui Intent to Recommend: (Studi Kasus Pada Produk Focallure di Kecamatan Jampang Tengah) - Lia Amelia; Mulfi Sandi Yuda (PT. Alahyan Publisher Sukabumi, 2026)
The development of social media has encouraged cosmetic brands like Focallure to utilize Influencer marketingas a marketing strategy. This study aims to analyze the influence of Influencer marketingand product quality on purchasing decisions through the Intent To Recommend of Focallure consumers in Jampang Tengah District. The study used a quantitative approach with a survey method of 100 respondents who used Focallure products. Data were collected through an online questionnaire and analyzed using path analysis and the Sobel Test. The results showed that Influencer marketingand product quality had a positive and significant effect on the Intent To Recommend and purchase decisions. In addition, the Intent To Recommend was proven to mediate the influence of Influencer marketingand product quality on purchasing decisions. The research variables were able to explain 75.5% of the variation in purchasing decisions. This study provides implications for Focallure to optimize collaboration with credible influencers and improve product quality to strengthen consumer purchasing decisions.